Antibacterial activity of ZnO nanoparticle coatings formed by electrophoretic deposition. (July 2020) - Uribe, P A; Ruiz, J; Ortiz, C C; Blanco, S I; Gutierrez, J A
Abstract: The scientific community is focused on the development and use of new nanomaterials to create novel devices and systems that can be useful to solve problems or provide services. Among all nanomaterials, semiconductors allow improving optical, electrical, and catalytic properties of several surfaces, including the corrosion resistance of the materials; corrosion causes several problems and economic losses in the food, pharmaceutical, and hospital industries because the materials selected must be durable, economic, and as innocuous as possible. Zinc oxide (ZnO) is one of the most interesting materials, is a photo-chemically active n-type semiconductor and has particular defects into intrinsic lattices, such as Zn and O vacancies. Herein, we use electrophoretic deposition (EPD) for the synthesis of nanostructured films composed of ZnO nanoparticles (ZnONPs) as a protective coating on low-alloy carbon steel. The electrochemical stability of the coated steel was evaluated and compared with the response of the bare steel. This work used NPs formed in homogeneous media and in reverse micelles (RMs) formed in our previous published report. The coatings were synthesized on the surface of SAE 1020 carbon steel electrodes with 12 mm diameter. As results, two different colloidal systems were formed, by RMs we synthesized high mono-dispersed and spherical 3-5 nm ZnONPs, and by homogeneous media anisotropic 20-100 nm ZnONPs, both systems with excellent fluorescence emission at different excitation wavelengths. The electrochemical evaluation confirms the stability of the coatings obtained, improving the corrosion resistance of the low-alloy carbon steel. We found that the coating obtained with the smallest particles shows better protective properties; the difference between both coatings could be related to the force balance during the electrophoretic deposition, where the friction force, that is against the electrophoretic movement, is proportional to the particle size, reducing the amount of deposited material.